2021
DOI: 10.21203/rs.3.rs-646031/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cross-reactivity of antibodies from non-hospitalized COVID-19 positive individuals against the native and B.1.351 SARS-CoV-2 spike proteins

Abstract: SARS-CoV-2 variants of concern (VOCs) have emerged worldwide, with implications on the spread of the pandemic. Characterizing the cross-reactivity of antibodies against these VOCs is necessary to understand the humoral response of non-hospitalized individuals previously infected with SARS-CoV-2, a population that remains understudied. Thirty-two SARS-CoV-2-positive (PCR-confirmed) and non-hospitalized Canadian adults were enrolled 14-21 days post-diagnosis in 2020, before the emergence of the B.1.351 VOC (also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Nonetheless, the fact that we could still detect antibodies with neutralization potency against the Wuhan strain-based pseudo virus throughout the six months of follow up in this longitudinal study indicates a good level of cross reactivity across the different variants as reported elsewhere (62). Further assessment of cross-neutralization among different variants will be important in understanding the extent of infection induced immunity in providing protection from future SARS-CoV-2 variants during periods of high transmission, as well as the effectiveness of the current SARS-CoV-2 vaccines.…”
Section: Discussionsupporting
confidence: 82%
“…Nonetheless, the fact that we could still detect antibodies with neutralization potency against the Wuhan strain-based pseudo virus throughout the six months of follow up in this longitudinal study indicates a good level of cross reactivity across the different variants as reported elsewhere (62). Further assessment of cross-neutralization among different variants will be important in understanding the extent of infection induced immunity in providing protection from future SARS-CoV-2 variants during periods of high transmission, as well as the effectiveness of the current SARS-CoV-2 vaccines.…”
Section: Discussionsupporting
confidence: 82%
“…A small mutation in the virus can turn monoclonal antibodies blind to the virus, and if the majority of the immune system is occupied with one specific antigen, they might miss a mutated virus and opportunistic bacteria. Heterologous immune training with BCG is considered responsible for reduced mortality from different respiratory infections in BCG‐vaccinated populations [ 11 , 12 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Equal volumes of EDC (400 mM in DI water) and NHS (100 mM in DI water) solutions were thoroughly mixed for less than one minute and immediately injected onto the SPR chip. Activation of the peptide monolayer with the EDC-NHS solution was performed for 2 minutes before the solution was washed away with a 10 mM sodium acetate buffer at pH 4.5 prior to injection of the capture protein (20 µg mL −1 in 10 mM sodium acetate buffer, pH 4.5, 17,18 Fisher scientific). The capture protein solution was left in the cell for 20 minutes to bind the carboxyl surface via its primary amino group and then washed out with the 10 mM sodium acetate buffer at pH 4.5.…”
Section: Spr Experimentsmentioning
confidence: 99%